Genetic Associations of Chronotype in the Finnish General Population - Maukonen, Mirkka; Havulinna, Aki S; Männistö, Satu; Kanerva, Noora; Salomaa, Veikko; Partonen, Timo (Journal of biological rhythms, 2020)
Individuals with a later chronotype (evening types) tend to have unhealthier behaviors and increased morbidity and mortality as compared with those with an earlier chronotype (morning types). However, the role of genetics in explaining evening types' adverse health and health behavior is unclear. Our aim was to study genetic associations of chronotype among 8433 Finns from the cross-sectional National FINRISK 2007 and 2012 studies. First, we studied associations between chronotype and 20 key clock genes with a candidate-gene approach and then performed a full genome-wide association study (GWAS) of chronotype. We also developed a genetic risk score (GRS) for chronotype based on 313 single nucleotide polymorphisms (SNPs) that have previously been associated with chronotype. Chronotype was assessed with a shortened version of Horne and Östberg's Morningness-Eveningness Questionnaire (sMEQ), and for comparison, we also used the single self-evaluation question on chronotype from the questionnaire. Linear and logistic regression was used for statistical analysis assuming additive effects. The clock gene analysis revealed 1 independent association signal within NR1D2 (lead SNP rs4131403) that was associated with chronotype (p < 0.05; as based on both chronotype assessment methods). The GWAS analysis did not yield any genome-wide significant associations (p > 5 × 10-8). However, higher GRS was associated with evening chronotype (p < 0.001; as based on both chronotype assessment methods). In conclusion, our findings indicated novel genetic associations between chronotype and the NR1D2 clock gene, which has previously been associated with carbohydrate and lipid metabolism. Furthermore, the GRS was able to capture the genetic aspect of chronotype in our study population. These findings expand our knowledge of the genetic basis of chronotype.Individuals with a later chronotype (evening types) tend to have unhealthier behaviors and increased morbidity and mortality as compared with those with an earlier chronotype (morning types). However, the role of genetics in explaining evening types' adverse health and health behavior is unclear. Our aim was to study genetic associations of chronotype among 8433 Finns from the cross-sectional National FINRISK 2007 and 2012 studies. First, we studied associations between chronotype and 20 key clock genes with a candidate-gene approach and then performed a full genome-wide association study (GWAS) of chronotype. We also developed a genetic risk score (GRS) for chronotype based on 313 single nucleotide polymorphisms (SNPs) that have previously been associated with chronotype. Chronotype was assessed with a shortened version of Horne and Östberg's Morningness-Eveningness Questionnaire (sMEQ), and for comparison, we also used the single self-evaluation question on chronotype from the questionnaire. Linear and logistic regression was used for statistical analysis assuming additive effects. The clock gene analysis revealed 1 independent association signal within NR1D2 (lead SNP rs4131403) that was associated with chronotype (p < 0.05; as based on both chronotype assessment methods). The GWAS analysis did not yield any genome-wide significant associations (p > 5 × 10-8). However, higher GRS was associated with evening chronotype (p < 0.001; as based on both chronotype assessment methods). In conclusion, our findings indicated novel genetic associations between chronotype and the NR1D2 clock gene, which has previously been associated with carbohydrate and lipid metabolism. Furthermore, the GRS was able to capture the genetic aspect of chronotype in our study population. These findings expand our knowledge of the genetic basis of chronotype.